2006
DOI: 10.1074/jbc.m510886200
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Regulatory Domains of cGMP-dependent Protein Kinase Iα and Iβ Retain Dimerization and Native cGMP-binding Properties and Undergo Isoform-specific Conformational Changes

Abstract: Molecular mechanisms that provide for cGMP activation of cGMP-dependent protein kinase (PKG) are unknown. PKGs are dimeric; each monomer contains a regulatory (R) and catalytic (C) domain. In this study, isolated recombinant R domains of PKGI␣-(⌬349 -670) and PKGI␤-(⌬364 -685) containing the dimerization and autoinhibitory subdomains and two allosteric cGMP-binding sites were expressed in Sf9 cells. Both R domains were dimers with elongated conformations (Stokes radii of 44 and 51 Å , respectively, and frictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…1C Inset). Previous studies using hydrodynamic and small-angle x-ray scattering techniques support our findings that cGMP binding to the regulatory domain of PKG I induces substantial conformational changes (27)(28)(29). ␣-FlincG was developed by attaching the entire regulatory domain of PKG I ␣ (residues 1-356) to cpEGFP (Fig.…”
Section: Resultssupporting
confidence: 69%
“…1C Inset). Previous studies using hydrodynamic and small-angle x-ray scattering techniques support our findings that cGMP binding to the regulatory domain of PKG I induces substantial conformational changes (27)(28)(29). ␣-FlincG was developed by attaching the entire regulatory domain of PKG I ␣ (residues 1-356) to cpEGFP (Fig.…”
Section: Resultssupporting
confidence: 69%
“…In original CEM cells we observed the expression of the mixed leukemia peptides that belongs to the group of histone-modifying enzymes and are involved in the pathogenesis of human leukemia [19]. Based on MS studies of cells treated with Herceptin, we identified cyclic GMP protein indicating possible changes in HER-2 receptor structure after treatments [20]. As a result of the treatment with anti-HER-2 (clone CB-11), we observed peptides that suggest increased transcription rates and belong to AP-2B receptor and ATP-binding cassette that transport a diverse set of substrates across membranes [21].…”
Section: Resultsmentioning
confidence: 98%
“…This was accompanied by a loss in solvent accessibility of the cGMP binding sites, suggesting a dramatic change in the structure of PKG1a in which the N-terminal and catalytic domain move apart during classical allosteric activation. Gel filtration studies have also shown that when cGMP binds PKG1a that the kinase elongates, consistent with a structural change that would expose the catalytic site (48).…”
Section: Cgmp-dependent Protein Kinasementioning
confidence: 95%